Kultur Jaringan Jeruk Keprok Tejakula (Citrus reticulata var. Tejakula) Menggunakan Tunas Muda dan Biji Serta Deteksi CVPD dengan Teknik Polymerase Chain Reaction (PCR) - VLORA VERONICA SIPANGKAR; I NYOMAN WIJAYA; MADE SRITAMIN (Fakultas Pertanian Universitas Udayana, 2020)
Tissue Culture Citrus (Citrus reticulata var. Tejakula) using Shoot and Seed and the Detection of CVPD with Polymerase Chain Reaction (PCR). The sample was taken in Pecatu Village, Kuta Selatan District, Badung Regency and continued with in vitro culture and PCR analysis at UPT. Genetic Resource and Molecular Biology Laboratory, was start from December of 2018 until May of 2019. The purpose of this research was to create a CVPD free Citrus reticulata var. Tejakula seedling from tissue culture. The sample was chosen based on visual characteristic. Two samples were taken from citrus plant that show CVPD symptoms and citrus plant that did not show CVPD symptoms. The seed and shoot were cultured using MS media for 12 week after planting (WAP). From this research showed that both explant from the shoot and seed were able to grow well. The explant from citrus sample that showed CVPD symptoms was infected by Liberibacter asiaticus and the explants from citrus that did not show CVPD symptoms was not invected by Liberibacter asiaticus, according to PCR analysis.